2021
DOI: 10.7759/cureus.14867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravenous Vitamin C Administration in Reducing Severity of Symptoms in Breast Cancer Patients During Treatment

Abstract: Introduction Alternative medicine during treatment is often used to make the quality of life (QoL) better. Women with early-stage breast cancer, particularly the ones who possess lower QoL, are more prone to opt for complementary medicine. This study aims to explore the effects exerted by intravenous vitamin C (IVC) on symptoms and adverse events associated with breast cancer treatment. Methods This single-center, parallel-group, single-blind interventional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For instance, a retrospective, multicentre, epidemiological cohort study [ 18 ] showed amelioration of appetite, fatigue, depression and sleep disorders in breast cancer and terminal cancer patients suffering from a wide variety of cancer types that received complementary 7.5 g IVC while being treated by respective standard regimens. More recently, a single-center, parallel-group, single-blind interventional study also in breast cancer patients [ 86 ] showed a similar and significant reduction of symptoms such as nausea, fatigue, tumor pain and loss of appetite by administering 25 g of IVC per week in addition to their current standard treatment. Favourably, no new side effects were reported after initiation of IVC treatment.…”
Section: High-dose Vitc As a Single Agentmentioning
confidence: 95%
“…For instance, a retrospective, multicentre, epidemiological cohort study [ 18 ] showed amelioration of appetite, fatigue, depression and sleep disorders in breast cancer and terminal cancer patients suffering from a wide variety of cancer types that received complementary 7.5 g IVC while being treated by respective standard regimens. More recently, a single-center, parallel-group, single-blind interventional study also in breast cancer patients [ 86 ] showed a similar and significant reduction of symptoms such as nausea, fatigue, tumor pain and loss of appetite by administering 25 g of IVC per week in addition to their current standard treatment. Favourably, no new side effects were reported after initiation of IVC treatment.…”
Section: High-dose Vitc As a Single Agentmentioning
confidence: 95%
“…One possible explanation is that oral vitamin C does not achieve the required plasma concentration to exert an anti-cancer effect, unlike IV. Indeed, orally administered vitamin C achieves maximum plasma concentrations of no more than 220 μmol/L of blood, while high-dose IV vitamin C generates plasma concentrations up into the millimolar range (≥15 mmol/L), leading to different outcomes [ 16 , 21 , 22 ]. Yeom et al, evaluated the quality of life of 39 terminal cancer patients who received high dose vitamin C (10 g twice by IV and 4 g oral daily intake for a week).…”
Section: Resultsmentioning
confidence: 99%
“…Cancers can influence patients' quality of life, and vitamin C is shown to positively affect pain relief and well‐being 39,40 . Moreover, vitamin deficiency is a common condition in patients with cancer, and anti‐neoplastic syndrome medications can also improve vitamin C deficiency and well‐being 41 .…”
Section: Cancermentioning
confidence: 99%
“…Moreover, vitamin deficiency is a common condition in patients with cancer, and anti‐neoplastic syndrome medications can also improve vitamin C deficiency and well‐being 41 . Constitutional manifestations such as fatigue, depression, nausea, pain and loss of appetite are common in patients with cancer, and it was shown that intravenous administration of vitamin C reduces these complications and has palliative applications 40,42 . Altogether, high‐dose vitamin C was shown to prolong the survival duration of patients, better performances and less pain compared to the control patients without receiving vitamin C 42 …”
Section: Cancermentioning
confidence: 99%